Implementasi Taktik Marketing Public Relations pada Rumah Sakit Swasta di Kota Bandung dalam membangun Brand Awareness - Renata Anisa; Retasari Dewi; Yustikasari Yustikasari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The growth in the number of hospitals in Indonesia and the development of hospital products and services that are increasingly developing also encourage competition in the health industry. Marketing public relations (MPR) is a strategy that can encourage purchases with trustworthy communication. MPR is able to build relationships with stakeholders, increase awareness, build brands, increase loyalty and build corporate reputation. The purpose of this research is to describe the marketing public relations tactics used by hospitals in Bandung City in building brand awareness. The method used in this research is qualitative with a descriptive study with data collection techniques of literature study, observation, and in-depth interviews with the hospital's marketing team. The results showed that hospitals use various marketing public relations (MPR) tactics to build brand awareness, namely marketing promotions, health promotions, coaching, and collaboration. The marketing public relations media used by the hospital are internal media and digital media to reach a wider public.